2014
DOI: 10.1890/13-2269.1
|View full text |Cite
|
Sign up to set email alerts
|

Fitness maximization by dispersal: evidence from an invasion experiment

Abstract: Abstract. Dispersal is essential for population persistence in transient environments. While costs of dispersal are ubiquitous, individual advantages of dispersal remain poorly understood. Not all individuals from a population disperse, and individual heterogeneity in costs and benefits of dispersal underlie phenotype-dependent dispersal strategies. Dispersing phenotypes are always expected to maximize their fitness by adaptive decision making relative to the alternative strategy of remaining philopatric. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 55 publications
1
53
0
Order By: Relevance
“…Such phenotypic differences have frequently been reported [7] and are known to affect the balance between the costs and benefits of dispersal [39]. Recent studies have shown that natural selection may favour the associations between dispersal and other phenotypic traits allowing individuals to reduce dispersal costs and thus lead to the evolution of dispersal syndromes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Such phenotypic differences have frequently been reported [7] and are known to affect the balance between the costs and benefits of dispersal [39]. Recent studies have shown that natural selection may favour the associations between dispersal and other phenotypic traits allowing individuals to reduce dispersal costs and thus lead to the evolution of dispersal syndromes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Freshly matured females constitute the dispersing phenotype in this species (Smitley & Kennedy ; Li & Margolis ; Bonte et al . ; Fronhofer et al . ; Van Petegem et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of measuring fitness of dispersal-related traits, fitness should be assessed in natal and colonized environments and the causes of any fitness variation, as they relate to the phenotypes and behaviours of individuals, their relatedness, the population density, and environmental quality of the different sites, need to be identified and quantified (Stinchcombe et al, 2002;Bonte et al, 2014).…”
Section: Using Multivariate Selection To Ask When Dispersal Is mentioning
confidence: 99%
“…Determining the relative importance of these factors has been the primary objective of recent empirical studies on the evolutionary causes of dispersal (e.g. Matthysen, 2012;Bitume et al, 2013;Bonte et al, 2014). The emerging synthesis of the ecology and evolution of dispersal emphasizes how these selective processes can lead to individual differences in multiple traits and behaviours related to their dispersal patterns, and that the evolution of dispersal can only be understood in the context of multiple life-history traits (Clobert et al, 2009Bonte et al, 2012;Stevens et al, 2012;Buoro & Carlson, 2014).…”
Section: Introductionmentioning
confidence: 99%